'Pleomorphic adenoma of the tongue: A common entity at the uncommon location'. (February 2019) - Chhabra, Sonia; Bhutani, Namita; Jain, Promil; Gill, Meenu; Nishith, Nilay; Sen, Rajeev
Abstract: The salivary gland tumors comprise of 3% of head and neck tumors. Pleomorphic adenoma, also known as mixed tumor, is the most common benign neoplasm of the major and minor salivary glands. The occurrence of pleomorphic adenoma of the tongue is very rare, and very few cases have been reported in the literature. A 41-year-old male presented with swelling on tongue. Cytological and histological examination revealed pleomorphic adenoma. Complete excision of the mass was done transorally under general anaesthesia. High index of suspicion and an adequate clearance of the tumor with a cuff of surrounding dispensable normal tissues is the key to successful treatment of such tumors. The authors consider the rarity of this case and present a rare case of pleomorphic adenoma of the tongue. Highlights: The salivary gland lesions pose a challenge to even the most experienced clinician and pathologist. Pleomorphic adenomas of the tongue are very rare accounting for 0 to 2.5% of the cases. The high recurrence rate and frequent malignant conversion are its characteristics features. High index of suspicion and an adequate clearance of the tumor is the key to successful treatment of such tumors.